Azithromycin 1% Ophthalmic Solution for Treatment of Blepharitis - Sharma, Srijana Pradhan; Jun, Cai Xiao (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Blepharitis is characterized by chronic inflammation of the lid margins, which may appear as simple hyperemia or as a true inflammation. It may occur in two forms anterior and posterior. The eyelid margins can become inflamed, irritated, and itchy when these glands produce abnormal secretions. Blepharitis is often seen in patients with acne rosacea, a generalized illness of oil glands. Anterior blepharitis is due to inflammation of the lid margin around the lashes. Seborrhoeic blepharitis is similar to dandruff of the scalp. Staphylococcal blepharitis is a result of bacterial infection of the lashes. Allergies due to reactions from mascara, contact lens solutions, and sprays, exposure to animals, environmental chemicals, or airborne allergens can also cause blepharitis. The single most important treatment principle is a daily routine of good eyelid hygiene ,this includes frequent scalp and face washing, using warm compresses to soak the eyelids, and doing eyelid scrubs but these treatment have very little efficacy in chronic and severe blepharitis. Antibiotic oral and ointment are also prescribed to decrease the bacterial load, other treatment modalities like artificial tear for dry eye and topical antibiotics are used in cases of severe inflammation. Topical antibiotics are recommended to decrease the bacterial load, and topical corticosteroids may help in cases of severe inflammation. Azithromycin ophthalmic solution 1% in Durasite has been proposed as a novel treatment for posterior blepharitis. In this review I shall focus on Azithromycin 1% ophthalmic solution for the treatment of blepharitis based on its good anti-infective, anti-inflammatory and good tissue penetration.